POWER QUALITY IMPROVEMENT IN A GRID CONNECTED RENEWABLE ENERGY SYSTEM - Mr. Anantrao V. Patil; Dr. Anwar M. Mulla; Mr. Swapnil D. Patil; Mr. Ajit B. Jadhav (International Journal of Innovations in Engineering Research and Technology, 2022)
In distributed system, renewable energy resources (RES) are progressively incorporated using power electronics interfaces. Extensive use of power electronics devices produce harmonic current and may reduce quality of power. In this paper, renewable energy resources (RES) is linked to the grid through a grid interfacing inverter for power quality improvement. The grid interfacing inverter is linked to a 3- phase 4-wire system and hysteresis current control method is used to generate gate pulses. Here renewable energy resource (RES) is represented as a dc source. The grid interfacing inverter has the capability of injecting RES power to the grid and also reduces load unbalance, load harmonics and reactive power demand is compensated. Total Harmonic Distortion (THD) of the grid connected system is analyzed. The simulation has been carried out in MATLAB/Simulink.